2017
DOI: 10.1038/s41598-017-14395-9
|View full text |Cite|
|
Sign up to set email alerts
|

WNT-activated bone grafts repair osteonecrotic lesions in aged animals

Abstract: The Wnt pathway is a new target in bone therapeutic space. WNT proteins are potent stem cell activators and pro-osteogenic agents. Here, we gained insights into the molecular and cellular mechanisms responsible for liposome-reconstituted recombinant human WNT3A protein (L-WNT3A) efficacy to treat osteonecrotic defects. Skeletal injuries were coupled with cryoablation to create non-healing osteonecrotic defects in the diaphysis of the murine long bones. To replicate clinical therapy, osteonecrotic defects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Wnt signalling promotes bone formation by increasing the expression of proteins involved in osteogenic signalling, such RUNX2 and OCN. 27,40 Jing et al 41 developed a Wnt3a protein therapy to activate the Wnt pathway, thereby promoting transcription of osteogenic genes and accelerating fracture healing, 41,42 confirming these effects.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Wnt signalling promotes bone formation by increasing the expression of proteins involved in osteogenic signalling, such RUNX2 and OCN. 27,40 Jing et al 41 developed a Wnt3a protein therapy to activate the Wnt pathway, thereby promoting transcription of osteogenic genes and accelerating fracture healing, 41,42 confirming these effects.…”
Section: Discussionmentioning
confidence: 93%
“…41 An increase in Wnt signalling increases the bone mineral density of aged people. 42,44 Therefore, stimulation of Wnt signalling is sufficient to overcome these age-related defects and represents a potential treatment for osteonecrosis and fractures in aged patients. 42 In our study, higher levels of LEF-1 and Osx mRNAs and greater numbers of BrdU-, RUNX2-and OCN-positive cells in the ROIs were observed in adult and aged CA mice than in adult and aged WT mice on day 14 after fracture.…”
Section: Discussionmentioning
confidence: 99%
“… 32 It is noted that liposome-reconstituted recombinant human WNT3A protein has been used to treat osteonecrosis defect. 33 The expression of DACT1 is found in primary chondrocytes and vascular endothelial cells. 34 , 35 Käkönen and Mundy 36 found that CSF-1 could interact with osteoblast to regulate the RANK–RANKL pathway to stimulate osteoclast precursors, ultimately leading to osteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…32 It is noted that liposome-reconstituted recombinant human WNT3A protein has been used to treat osteonecrosis defect. 33 The expression of DACT1 is found in primary chondrocytes and vascular endothelial cells. 34,35 Käkönen and Figure 4 The sub-network of miRNA-target mRNAs between hsa-miR-378c, hsa-let-7a-5p, hsa-miR-28-5p, hsa-miR-3200-5p, hsa-miR-532-5p, and their targeted mRNAs in osteonecrosis of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt proteins rank amongst the most potent pro-osteogenic signals [ 42 44 ], which has directly led to the development of Wnt pathway activators for purposes of increasing bone mass [ 45 ] and accelerating bone repair [ 46 ]. For purposes of accelerating graft incorporation, however, systemic delivery of drugs such as romosozumab, an anti-Sclerostin antibody [ 47 ], is contraindicated because long-term use actually suppresses osteoprogenitor cell proliferation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%